Minor temperature shifts do not affect chromosomal ploidy but cause transcriptomic changes in Leishmania braziliensis promastigotes in vitro (2020)
BACKGROUND The leishmaniases are complex neglected diseases caused by protozoan parasites of the genus Leishmania. Leishmania braziliensis is the main etiological agent of cutaneous leishmaniasis in the New World. In recent studies, genomic changes such as chromosome and gene copy number variations (CNVs), as well as transcriptomic changes have been highlighted as mechanisms used by Leishmania species to adapt to stress situations. OBJECTIVES The aim of this study was to determine the effect of short-term minor temperature shifts in the genomic and transcriptomic responses of L. braziliensis promastigotes in vitro. METHODS Growth curves, genome and transcriptome sequencing of L. braziliensis promastigotes were conducted from cultures exposed to three different temperatures (24ºC, 28ºC and 30ºC) compared with the control temperature (26ºC). FINDINGS Our results showed a decrease in L. braziliensis proliferation at 30ºC, with around 3% of the genes showing CNVs at each temperature, and transcriptomic changes in genes encoding amastin surface-like proteins, heat shock proteins and transport proteins, which may indicate a direct response to temperature stress. MAIN CONCLUSIONS This study provides evidence that L. braziliensis promastigotes exhibit a decrease in cell density, and noticeable changes in the transcriptomic profiles. However, there were not perceptible changes at chromosome CNVs and only ~3% of the genes changed their copies in each treatment. © 2020, Fundacao Oswaldo Cruz. All rights reserved.